The new initiative of the East African Cooperation : opportunities, challenges and prospects - Kimemia, Peter Njau (Rhodes University, Faculty of Commerce, Department of Economics, 2000)
The landmark inauguration of the East African Cooperation (EAC) on 14 March 1996 brought to the fore some key issues regarding regional economic integration in East Africa, particularly since it signalled the second attempt by Kenya, Uganda and Tanzania to form a regional economic bloc. The EAC's predecessor, the East African Community, had collapsed in 1977 in acrimonious circumstances. Prominent among the issues that led to the collapse of the East African Community was the perception of unequal gains from the integration scheme, with Uganda and Tanzania considering that disproportionate benefits were accruing to Kenya at their expense. With the new initiative, the question emerges as to whether the problems that caused the collapse of the Community will not beset the EAC and subject it to a similar fate. In an attempt to address this question, this study considers some of the theoretical issues relating to regional economic integration among countries at different levels of development, and attempts to provide an analysis of the new initiative of the EAC in the light of this theory and the history of the East African Community. The study also critically examines the objectives of the EAC and the integration strategy adopted by the three countries, and offers suggestions on the way forward. Among the arguments made in this thesis are that, contrary to the suggestions of orthodox static analysis, if the dynamic effects of integration are considered, then there may be important gains which may accrue to integrating states in the developing country context. It is also argued that different levels of development among integrating states need not necessarily be an impediment to economic integration. The study finds that, in spite of the enormous challenges facing the EAC, member states may be better off within the integration scheme than if they acted as individual units in a rapidly globalizing international system.
Keywords: International economic relations; Africa, East -- Foreign economic relations; East African Co-operation; Africa, East -- Economic integration